2014
DOI: 10.1016/j.phrp.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Health Behavior and General Health Status: Based on 2011 Korea National Health and Nutrition Examination Survey

Abstract: ObjectivesThe aim of the present study is to investigate the relationship between health behavior and general health status.MethodsWe used data from the 2011 Korea National Health and Nutrition Examination Survey. Mental health was measured by stress recognition and depression. Dietary habit was measured by mixed grain diet. Life pattern was measured by sleeping time and working pattern. Physical activity was measured by walking and exercise. We defined general health status as Euro Quality of Life-5 Dimension… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
(6 reference statements)
1
3
0
1
Order By: Relevance
“…We demonstrated that most health behavior indicators have positive associations with the general health status of residents at the city level. Our findings are similar to those of an individual-level study based on the 2011 Korean National Health and Nutrition Examination survey, which reported that increases in individual healthy behaviors such as mixed-grain diet, sleeping hours, exercise, and walking were positively associated with increases in general health status (as defined by EuroQol-5 Dimension and EuroQol Visual Analogue Scale) (20). Also, in a 9-yr longitudinal study of individual working-age residents of Finland between 2003 and 2012, positive changes in health behaviors (physical activity, dietary habits, alcohol consumption, and smoking status) improved well-being, defined as interest, happiness, ease in life, and less perceived loneliness (21).…”
Section: Discussionsupporting
confidence: 88%
“…We demonstrated that most health behavior indicators have positive associations with the general health status of residents at the city level. Our findings are similar to those of an individual-level study based on the 2011 Korean National Health and Nutrition Examination survey, which reported that increases in individual healthy behaviors such as mixed-grain diet, sleeping hours, exercise, and walking were positively associated with increases in general health status (as defined by EuroQol-5 Dimension and EuroQol Visual Analogue Scale) (20). Also, in a 9-yr longitudinal study of individual working-age residents of Finland between 2003 and 2012, positive changes in health behaviors (physical activity, dietary habits, alcohol consumption, and smoking status) improved well-being, defined as interest, happiness, ease in life, and less perceived loneliness (21).…”
Section: Discussionsupporting
confidence: 88%
“…Health behaviors are closely linked to a person's general health. This is not only postulated in theoretical models like the determinants of health-model (1), but has also been shown empirically (2). In addition to the individual level, health behaviors also have large public health implications.…”
Section: Introductionmentioning
confidence: 68%
“…A research in Korea shows that sleeping duration of 6-9 hours can make people have high quality of life (QOL), low probability on suffering a disease, and the limit of sleeping time is <6 hours or > 9 hours. The stability of emotion, Normal weight eating habit, not smoking, avoiding alcohol, and enough resting is an important lifestyle for maintaining health status 14 . A research to male students in Nigeria shows that their daily sleeping duration is 7.42 hours/day, standing time of 1.92 hours/day, and private activity of 1.57 hours/day 15 .…”
Section: Discussionmentioning
confidence: 99%